How effective is game-based educational platform on students’ learning interest and mathematics problem-solving skills? Empirical evidence from Islamic boarding school - Desi Ratnasari; Lalu Sucipto; Muhammad Syawahid; Marini Kasim (Universitas Islam Negeri (UIN) Mataram, 2026)
[English]: This study aims to investigate the impacts of Kahoot, a game-based educational platform, on students’ learning interest and mathematical problem-solving abilities. The study employed a quantitative approach with a quasi-experimental research, specifically the non-equivalent control group design. The research population consisted of all seventh-grade students at a private junior high school in Indonesia, totaling 25 students which are selected through saturated sampling technique. The research instruments included a learning interest questionnaire and an essay-based test measuring mathematical problem-solving skills. Data were analyzed through multivariate assumption testing, followed by hypothesis testing using Multivariate Analysis of Variance (MANOVA). The results of the assumption tests indicated that: (i) the data satisfied the assumption of multivariate normality, (ii) the dependent variables demonstrated adequate intercorrelations for multivariate analysis, and (iii) the covariance matrices across groups exhibited homogeneous characteristics. Accordingly, the MANOVA outcomes revealed a significance value of less than 0.05 (p < 0.05), indicating that the use of Kahoot had a statistically significant effect, both simultaneously and partially, on students’ learning interest and mathematical problem-solving abilities. The research outcomes in this paper strengthened the past studies which claim that Kahoot can be utilized as an innovative instructional platform for teaching and learning mathematics. [Bahasa]: Penelitian ini bertujuan mengetahui dampak penggunaan platform game edukasi, Kahoot, terhadap minat belajar dan pemecahan masalah matematika siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis quasi experiment dan desain non-equivalent control group. Populasi penelitian adalah seluruh siswa kelas VII di sekolah swasta menengah pertama di Indonesia berjumlah 25 siswa yang dipilih dengan teknik sampling jenuh. Instrumen penelitian berupa angket minat belajar dan tes uraian kemampuan pemecahan masalah. Data dianalisis melalui uji asumsi multivariat, kemudian dilanjutkan dengan uji hipotesis menggunakan Multivariate Analysis of Variance (MANOVA). Hasil uji asumsi menunjukkan bahwa (i) data memenuhi asumsi normalitas multivariat, (ii) variabel dependen memiliki hubungan yang memadai untuk dianalisis secara multivariat, dan (iii) matriks kovarians antar kelompok menunjukkan karakteristik homogen. Selanjutnya,hasil uji MANOVA menunjukkan nilai signifikansi < 0.05 sehingga dapat disimpulkan bahwa penggunaan media Kahoot berpengaruh signifikan, baik secara simultan maupun parsial, terhadap minat belajar dan kemampuan pemecahan masalah matematis siswa. Temuan penelitian ini memperkuat penelitian-penelitian terdahulu yang menyatakan bahwa Kahoot dapat dimanfaatkan sebagai media inovatif untuk pengajaran dan pembelajaran matematika.